STUDY OF THE INTERNAL - EXTERNAL ENVIRONMENT OF COLLEGE AFTTER THE END OF THE PEAK OF THE COVID -19 PANDEMIC - Wijiharta Wijiharta; Siti Murtiyani; Salihah Khairawati; Muhajirin Muhajirin (At-Tauzi : Jurnal Ekonomi Islam, 2022)
This study aims to conduct a study of the organization's internal and external environment after the outbreak of the COVID-19 pandemic. This study took the object of the tertiary institution of the Islamic Economics College (STEI) Hamfara. The research method used is qualitative. The technique of collecting data is through a group discussion forum (FGD) with the subject of the leadership ranks. The results of the study concluded that the study of the internal and external environment showed that the impact of the pandemic on the organization was still indicated. Dramatic environmental changes such as a pandemic can have both positive and negative impacts. Based on the results of the study of the organizational environment, STEI Hamfara is in a position of opportunity with a balance of strengths and weaknesses of internal conditions, with an opportunity position from the external side. This position requires caution in managing and improving the organization's internal as well as selective and strategic considerations in taking advantage of various opportunities.